Hierarchical Self-Assembly of One-Dimensional Streptavidin Bundles as a Collagen Mimetic for the Biomineralization of Calcite - Burazerovic, Sabina; Gradinaru, Julieta; Pierron, Julien; Ward, Thomas R. (My University, 2007)
We report on our efforts to create efficient artificial metalloenzymes for the enantioselective hydrogenation of N-protected dehydroamino acids using either avidin or streptavidin as host proteins. Introduction of chiral amino acid spacers - phenylalanine or proline - between the biotin anchor and the flexible aminodiphosphine moiety 1, combined with saturation mutagenesis at position S112X of streptavidin, affords second generation artificial hydrogenases displaying improved organic solvent tolerance, reaction rates (3-fold) and (S)-selectivities (up to 95 % ee for N-acetamidoalanine and N-acetamidophenylalanine). It is shown that these artificial metalloenzymes follow Michaelis-Menten kinetics with an increased affinity for the substrate and a higher kcat than the protein-free catalyst (compare kcat 3.06 min-1 and KM 7.38 mM for [Rh(COD)Biot-1]+ with kcat 12.30 min-1 and KM 4.36 mM for [Rh(COD) Biot-(R)-Pro-1]+ WT Sav). Finally, we present a straightforward protocol using Biotin-Sepharose to immobilize artificial metalloenzymes (>92 % ee for N-acetamidoalanine and N-acetamidophenylalanine using [Rh(COD) Biot-(R)-Pro-1]+ Sav S112W).
Keywords: biomineralization; calcite; coordination polymers; metal-organic protein frameworks; protein structures